The apparatus performance of the Tataaran Satu Urban Village Office, South Tondano Sub-District, Minahasa Regency - Winadio, Swasti Yogi; Mamonto, Fitri; Kandouw, Selphius (Technium Social Sciences Journal, 2023)
This study aims to find out how the performance of the Tataaran Satu Urban Village apparatus, South Tondano Sub-District, Minahasa Regency, especially non-ASN, which includes the Head of the Environment and the Assistant Head of the Environment, is seen from work productivity which has the main dimensions, namely Attitude, Ability and Work Enthusiasm. The method used is a qualitative research method. This research was conducted in the Tataaran Satu Urban Village, South Tondano Sub-District, Minahasa Regency. The focus in this study is related to the performance of the Tataaran Satu Urban Village apparatus which includes the Head of the Neighborhood and the Assistant Head of the Neighborhood in providing services to the people of the Tataaran Satu Urban Village, South Tondano Sub-District, Minahasa Regency. Data collection techniques are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions.The results of the study show that a) the performance of the Urban Village apparatus when viewed from their attitude, they are able to communicate well with the people they lead, are polite, like to greet Satu another. Also there are those who are still shy in giving announcements or in greetings to the public. b) The performance of Urban Village apparatus, when viewed from Capability, can be concluded that the performance of Urban Village apparatus is still lacking in terms of ability, for example in computer operation, how to deliver remarks, announcements and directions that cannot be conveyed properly to the Tataaran Satu Urban Village community. c) The performance of village officials, when viewed from work enthusiasm, it can be concluded that the performance of village officials is still lacking in terms of enthusiasm, such as prioritizing their main work, hard to find when needed and many reasons if given an assignment by the leadership. Factors that impede performance are 1) Lack of work motivation, so that it can affect the community in community involvement in community activities. 2) Did not receive training and development so that the village officials did not know what to do when they were appointed as village officials. 3) The average age of village officials is 50 years. 4) There are no fixed regulations or rules for evaluating the performance of non-ASN Urban Village officials.